DNase-Sensitive and -Resistant Modes of Biofilm Formation by Listeria monocytogenes - Zetzmann, Marion; Okshevsky, Mira; Endres, Jasmin; Sedlag, Anne; Caccia, Nelly; Auchter, Marc; Waidmann, Mark S.; Desvaux, Mickaël; Meyer, Rikke L.; Riedel, Christian U. (Frontiers in Microbiology, 2015)
Listeria monocytogenes is able to form biofilms on various surfaces and this ability is thought to contribute to persistence in the environment and on contact surfaces in the food industry. Extracellular DNA is a component of the biofilm matrix of many bacterial species and was shown to play a role in biofilm establishment of L. monocytogenes. In the present study, the effect of DNaseI treatment on biofilm formation of L. monocytogenes EGD-e was investigated under static and dynamic conditions in normal or diluted complex medium at different temperatures. Biofilm formation was quantified by crystal violet staining or visualized by confocal laser scanning microscopy. Biomass of surface-attached L. monocytogenes varies depending on temperature and dilution of media. Interestingly, L. monocytogenes EGD-e forms DNase-sensitive biofilms in diluted medium whereas in full strength medium DNaseI treatment had no effect. In line with these observations, extracellular DNA is present in the matrix of biofilms grown in diluted but not full strength medium and supernatants of biofilms grown in diluted medium contain chromosomal DNA. The DNase-sensitive phenotype could be clearly linked to reduced ionic strength in the environment since dilution of medium in PBS or saline abolished DNase sensitivity. Several other but not all species of the genus Listeria display DNase-sensitive and -resistant modes of biofilm formation. These results indicate that L. monocytogenes biofilms are DNase-sensitive especially at low ionic strength, which might favor bacterial lysis and release of chromosomal DNA. Since low nutrient concentrations with increased osmotic pressure are conditions frequently found in food processing environments, DNaseI treatment represents an option to prevent or remove Listeria biofilms in industrial settings.